Headache in a young woman: leptomeningeal metastasis as the first presentation of underlying breast malignancy. (6th May 2015) - Mohan, Poornima; Antonelou, Marilina; Dadzie, Ophelia; Dubrey, Simon
Abstract : A 37-year-old woman presented with a 2-week history of persistent headache in an occipitotemporal distribution. The patient had experienced prior headaches and migraines, but this presentation was characterised by its intensity and duration. There was associated dizziness and blurring of vision in episodes occurring up to 4–5 times per day. Whole body cross-sectional CT imaging and MRI of neuronal axes were normal. Cerebrospinal fluid cytology demonstrated large abnormal pleomorphic cells expressing the tumour marker CA125. Positron emission tomography-fluorodeoxyglucose revealed bilateral axillary and cervical lymphadenopathy as well as increased uptake in the lateral regions of both breasts. These results correlated with MRI breast and mammography findings. Axillary lymph node biopsy showed poorly differentiated adenocarcinoma making the diagnosis of breast malignancy, the most likely primary site of metastatic leptomeningeal disease. In the 6-week interval between initial presentation and diagnosis, the patient deteriorated significantly with the new onset of facial nerve palsy and partial seizures. The treatment intent was palliative, focusing on symptom control with systemic chemotherapy and whole brain radiotherapy.